Investigating a novel CMOS ring oscillator with LC-feedbacks - Tan Lu; Weijie Zhu; Wanjing Zhu; Jianguo Ma (2010 IEEE International Conference of Electron Devices and Solid-State Circuits, 2010)
CMOS ring oscillators have important advantages for what it has gained public notice. However, the performance of CMOS ring oscillators usually suffers from an intrinsic poor phase noise characteristic. This paper makes some investigation of a novel CMOS ring oscillator with LC-feedbacks. The analysis indicates that the proposed novel CMOS ring oscillator has a better phase noise performance and this was supported by simulation results.